Activation of cannabinoid receptor 2 by turmeric oleoresin reduces inflammation and oxidative stress in an osteoarthritis in vitro model - Ghiselli, Federico; Majer, Roberta; Piva, Andrea; Grilli, Ester (Frontiers in Pharmacology, 2024)
Osteoarthritis (OA) is a chronic condition characterized by the progressive degradation of articular cartilage, leading to pain and reduced mobility. Turmeric, a well-established traditional medicinal plant, has demonstrated anti-osteoarthritic properties in various OA models and clinical settings. This study aimed to explore the molecular mechanisms underlying these effects by investigating the potential of turmeric oleoresin (TUR) to activate Cannabinoid Receptor 2 (CBR2) and its role in mediating TUR's anti-inflammatory and antioxidant effects using an in vitro OA model. Molecular docking and cAMP quantification confirmed that TUR functions as a CBR2 agonist. The study further assessed the impact of TUR on oxidative stress levels, inflammatory markers, and the expression of key endocannabinoid system components, including enzymes and receptors, in human chondrosarcoma cells (SW-1353). Cells were exposed to menadione to induce oxidative stress or to a combination of IL-1β and TNF-α to stimulate inflammation, with TUR treatment administered both in the presence and absence of the CBR2 antagonist SR144528. TUR treatment significantly decreased reactive oxygen species (ROS) production and downregulated the expression of pro-inflammatory cytokines such as IL-6, as well as COX-2 and metalloproteases, all of which are critical to the progression of OA. Additionally, TUR treatment led to the suppression of key signaling pathways associated with OA pathogenesis, including the reduction of NFKB1, ERK 1/2, and c-Myc expression. These effects were significantly reversed upon CBR2 inhibition, underscoring the pivotal role of CBR2 in TUR's bioactivity. Furthermore, TUR enhanced the expression of HMOX-1, suggesting an involvement in antioxidant defense mechanisms, and altered the expression of endocannabinoidrelated enzymes such as DAGL-α and MAGL, highlighting the broader impact of TUR on the endocannabinoid system. These findings provide new insights into the molecular mode of action of turmeric as an anti-osteoarthritic agent, particularly through its interaction with CBR2.